2017
DOI: 10.1097/eja.0000000000000624
|View full text |Cite
|
Sign up to set email alerts
|

Background noise lowers the performance of anaesthesiology residents’ clinical reasoning when measured by script concordance

Abstract: Our study suggests that noise affects clinical reasoning of anaesthesiology residents especially junior residents when measured by SCT. This observation supports the hypothesis that noise should be prevented in operating rooms especially when junior residents are providing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…We chose to perform the study in medical students who were inexperienced with laparoscopy in order to reduce potential previous experience influencing laparoscopic task performance. Studies evaluating noise in the OR found higher subjective distraction levels in assisting surgeons with less experience compared to the main, more experienced surgeons [48], while the negative impact on clinical reasoning was lower when anesthesiological residents were more experienced [49]. It has been theorized that more experienced surgeons can block out noise and music more effectively [10], theoretically decreasing potential effect size and increasing the required number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to perform the study in medical students who were inexperienced with laparoscopy in order to reduce potential previous experience influencing laparoscopic task performance. Studies evaluating noise in the OR found higher subjective distraction levels in assisting surgeons with less experience compared to the main, more experienced surgeons [48], while the negative impact on clinical reasoning was lower when anesthesiological residents were more experienced [49]. It has been theorized that more experienced surgeons can block out noise and music more effectively [10], theoretically decreasing potential effect size and increasing the required number of participants.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] It has been proven that background noise inside the OR affects clinical reasoning, especially in junior residents. [ 11 ] It has also been shown that noise can generally have psychological and physiological effects on humans, especially when performing critical tasks. [ 32 ] We argue that outside cognitive distractions, such as described in our study, should be occasionally applied during lab training to provide a more realistic environment and to ensure that a satisfactory level of skill is achieved to provide resilience to the inevitable outside interference experienced during actual clinical surgery in the OR.…”
Section: Discussionmentioning
confidence: 99%
“…3,[15][16][17][18][19][20] Excessive noise in the health care environment may minimize the ability to communicate effectively, make it difficult to understand content, and contribute to miscommunication 15,21 that could potentially lead to an error. [22][23][24] The Environmental Protection Agency (EPA) recommends that the level of continuous background noise in hospitals not exceed 45 decibels (dB) during the day. The World Health Organization recommends that environmental noise levels not exceed 30 dB.…”
Section: Rationalementioning
confidence: 99%